If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 30 = 27 Reorder the terms: 30 + 9x = 27 Solving 30 + 9x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 9x = 27 + -30 Combine like terms: 30 + -30 = 0 0 + 9x = 27 + -30 9x = 27 + -30 Combine like terms: 27 + -30 = -3 9x = -3 Divide each side by '9'. x = -0.3333333333 Simplifying x = -0.3333333333
| 20-4(p+1.25)=5+p | | 0=-16x^2+16x+320 | | (2w+7)w=99 | | 0.3a+.7=.5a-.1 | | -8(3p+2)+2(-5+7p)=-66 | | 2(x-1)+3x=3(-2+x) | | 1.5*1= | | (2x^2+8x+1)= | | f(x)=15x+10 | | (2w+11)w=63 | | (8-z)(5z-9)=0 | | 5(1-8k)+4(3k+7)=61 | | 2w+11=63 | | -3-2x+5=5+x-2x | | 8+8(-2g+4)=4(-4g+10) | | 7-5(-7b-1)=-8(3-4b) | | 5+x(53)+8=52 | | -3x^2-6x-21=0 | | 13x+3=23+3x | | 7m(m-1)=3(1-m) | | g(b+8)=8x+5 | | (2w-5)w=33 | | X-3-3x=-3(1+x) | | (3x^2+22x-16)= | | -4(x+7)=4(-x+8) | | 12x^2+5x-98=0 | | g(-4b)=8x+5 | | 5(3n+5)+6(1-5n)=16 | | -5(x-4)+7(x-1)=23 | | x^2-20x+51= | | -x^2-12x-9=0 | | 6x+7=2x |